Antibody Targeting of “Steady-State” Dendritic Cells Induces Tolerance Mediated by Regulatory T Cells - Mahnke, Karsten; Ring, Sabine; Enk, Alexander H. (Frontiers in Immunology, 2016)
Dendritic cells (DCs) are often defined as pivotal inducers of immunity, but these proinflammatory properties only develop after stimulation or ex vivo manipulation of DCs. Under non-inflammatory conditions in vivo, DCs are embedded into a tissue environment and encounter a plethora of self-antigens derived from apoptotic material. This material is transported to secondary lymphoid organs. As DCs maintain their non-activated phenotype in a sterile tissue environment, interaction with T cells will induce rather regulatory T cells than effector T cells. Thus, DCs are not only inducers of immunity but are also critical for maintenance of peripheral tolerance. Therapeutically, intervention for the induction of long-lasting tolerance in several autoimmune conditions may therefore be possible by manipulating DC activation and/or targeting of DCs in their “natural” tissue environment.